On the use of the terminal-value approach in risk-value models - Gregor Dorfleitner (Annals of Operations Research, 2020)
We extend risk-value models for valuing streams of risky cash flows by establishing the well-known concept of terminal value in this context. For a constant growth assumption we are able to derive upper and lower bounds for the terminal value in the case of a translation-invariant and in the case of a position-invariant risk measure. For both cases we also obtain an exact formula under a special growth assumption for the future cash flows. Furthermore, we provide results on the applicability of the general findings for the case that the log-return of the risky investment follows a Brownian motion.
Keywords: 000; New approach; Business valuation; Project valuation; Terminal value; Risk measure